Clinical practice guidelines for the treatment of squamous cell carcinoma of the head and neck: an assessment based on the AGREE II, AGREE-REX tools and the RIGHT checklist - Zhang, Yingzhen; Liu, Junjie; Liu, Shuyu; Zhang, Ying; Su, Xingzhou; Huang, Shaohui; Duan, Weiyi (Frontiers in Oncology, 2024)
ObjectiveThe aim of this study was to obtain several published clinical practice guidelines (CPGs) for Head and neck squamous cell carcinoma (HNSCC) and critically assess and compare their quality by using three guideline quality evaluation tools, namely, AGREE II, AGREE-REX, and RIGHT, to support the development of future CPGs for HNSCC.MethodsClinical practice guidelines related to the diagnosis and treatment of HNSCC were screened through a comprehensive systematic literature search. Data were extracted from the guidelines which met the inclusion criteria, and two experienced head and neck oncology surgeons were trained to act as independent reviewers. The quality of the retrieved guidelines that met the inclusion and exclusion criteria was evaluated by using the AGREE II, AGREE-REX, and RIGHT tools. Then, the quality of the guidelines that met the criteria was assessed. Finally, conclusions and recommendations were drawn based on the scoring results.ResultsA total of eight guidelines met the inclusion criteria. Four guidelines(written by ASCO, NCCN, CCO and KCE) scored > 60% in five or more AGREE II quality domains, two guidelines(written by ASCO and KCE) scored > 60% in all AGREE-REX quality domains, and two guidelines(written by ASCO and KCE) scored > 60% in all quality domains on the RIGHT checklist and were considered “recommendable”.ConclusionsThe authors recommend consulting the American Society of Clinical Oncology guidelines for HNSCC and suggest that future guideline development groups refer to the guideline evaluation framework for guideline writing to enhance the applicability and effectiveness of clinical practice guidelines.